12-Month stability of neurological soft signs in stabilized patients with schizophrenia. (3rd October 2019) - Fountoulakis, Konstantinos N.; Panagiotidis, Panagiotis; Kimiskidis, Vasilios; Nimatoudis, Ioannis
Abstract: Objective: Neurological soft signs (NSS) are a group of minor non-localizable neurological abnormalities found more often in patients with schizophrenia. The aim of the current study was to investigate their temporal stability and relationship to the overall outcome over a 12-month period. Material and methods: The study sample included 133 stabilized patients suffering from schizophrenia (77 males and 56 females; aged 33.55 ± 11.22 years old). The assessment included the application at baseline and after 12 months of the Neurological Evaluation Scale (NES), and a number of scales assessing the clinical symptoms and adverse effects. The statistical analysis included ANOVA, exploratory t -test and Pearson correlation coefficients with Bonferroni correction. Results: In stabilized patients, NSS are stable over a 12-month period with only the subscale of NES-sensory integration manifesting a significant worsening, while, in contrast, most of the clinical variables improved significantly. There was no relationship of NES scores with the magnitude of improvement. The only significant negative correlation was between NES-motor coordination and Positive and Negative Syndrome Scale-GP change at 1 year. Discussion: The results of the current study suggest that after stabilization of patients with schizophrenia, there are probably two separate components, a 'trait' which is stable over a 12-month period, and a 'degenerative' component with a tendency to worsen probably in parallel with the progression of the illness and in correlation with the worsening of negative symptoms. However, the statistical support of the 'degenerative' component is weak. Significant outcomes: Neurological softs signs are stable over a 12-month period, with the exception of 'sensory integration' which manifests significant improvement irrespective of treatment response. They do not respond to treatment with antipsychotics. They do not constitute a prognostic factor to predict improvement over a period of 1 year. Neurological soft signs constitute a trait symptom of schizophrenia which is stable though time. Limitations: All the subjects have been previously hospitalized which may represent a more severe form of schizophrenia. Also, all patients were under antipsychotic and some also under benzodiazepine medications. Patients with comorbid somatic disorders were excluded which may decrease generalizability of results.